Nerve Blocks at the Wrist for Carpal Tunnel Release Revisited: The Use of Sensory-Nerve and Motor-Nerve Stimulation Techniques. Issue 6 (1st November 2005) - Macaire, Philippe; Choquet, Olivier; Jochum, Denis; Travers, Vincent; Capdevila, Xavier
Abstract : Background and Objectives: Because the median nerve at the wrist has mainly sensory endings, the aim of this study was to assess the response of the median nerve to nerve stimulation at the wrist and to evaluate the quality of median nerve block. A control group of patients who received blinded injections was analyzed and compared post hoc. Methods: One hundred and eleven patients scheduled for ambulatory endoscopic carpal-tunnel release performed under median and ulnar nerve blocks at the wrist were prospectively studied. The blocks were performed with a nerve stimulator. Nerve-stimulation techniques were explained to the patient before the block was performed. The patient was trained to inform the anesthetist of their perception of an electrical paresthesia that was synchronized to the nerve stimulator. The anesthetist recorded the first response of the patient to nerve stimulation: sensory (S), sensory-motor (SM), or motor response (M). When the minimal stimulating current was obtained, an equal volume of 4 mL of 1.5% mepivacaine was injected on median and ulnar nerves. If necessary, a lateral subcutaneous injection of 2 mL of 1.5% mepivacaine was administered at the wrist crease in the musculocutaneous nerve area. Thirty-five patients who received blinded local anesthetics injections were included post hoc. Quality of anesthesia was compared between groups. Results: Responses included 89 S (80.2%), 18 SM (16.2%), and 4 M (3.71%). No differences occurred in time to perform the block, minimal current intensity, and efficacy. More punctures were necessary in the M group compared with the S group and the control group ( P < .05). The onset time of sensory blocks increased significantly in control-group patients ( P < .05), but the duration of the nerve-block procedure decreased in comparison with the M group. Respectively, 10% and 20% of patients experienced mild or severe pain in the nerve-stimulation group and control group. At 20 minutes, the block was complete for the median and ulnar nerves in 96.4% and 85% of the nerve-stimulation patients and control patients ( P < .05). Two patients in the control group experienced painful mechanical paresthesia. Neither permanent nor transient nerve injuries were observed during or after the nerve block or surgery. Conclusion: This study describes how infrequently an initial motor response is identified when a nerve stimulator is used on the median nerve at the wrist. A very high success rate of median and ulnar nerve block at the wrist is obtained by use of sensory or sensory-motor-nerve stimulation and less than 10 mL of anesthetic solution.